Computed tomography of blunt spleen injury: a pictorial review - Hassan, Radhiana; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Sa'at@Yusof, Azlin (Universiti Sains Malaysia, 2011)
The spleenis one of the organs most frequently ijured in blunt abdominal trauma. Computed tomography (CT) scanning can accurately detect splenic injury and is currently the managing modality of choice in accessing clinically stable patients with blunt abdominal trauma. The CT features of spleen injury include Iaceration, subcapsular or parenchymal haematomas, active haemorrhage, and vascular injuries.We present a pictorial review of the spectrum of CT findings for blunt splenic injuries. This article will be a useful reference for radiologists and surgeons as CT scan is widely used for the accessment of splenic injuries and contributes to the current trend towards nonsurgical management of this injury